1989
DOI: 10.1101/gad.3.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of Drosophila myofibril formation: effects of actin and myosin heavy chain null alleles.

Abstract: We used null mutations of Drosophila actin and myosin genes to investigate two aspects of myofibril assembly.First, we eliminated all actin or myosin in flight muscles to evaluate contributions of thick and thin filaments to sarcomere formation. Results demonstrate that thick and thin filament arrays can assemble independently but that both are essential for sarcomeric order and periodicity. Second, we examined how filament stoichiometry affects myofibril assembly. We find that heterozygotes for actin (Act88F)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
98
1
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(115 citation statements)
references
References 24 publications
13
98
1
1
Order By: Relevance
“…If so, a mutation that alters the ratio of thick to thin filaments or affects crossbridge formation would also be expected to cause aberrant myofibrillar assembly. As expected, mutations in the genes encoding myosin heavy chain, troponin T and the IFM specific isoform of actin have been shown to result in aberrant myofibrillar assembly in heterozygotes (Mogami et al, 1981;Mahaffey et al, 1985; Chun and Falkenthal, 1988;O'Donnell and Bernstein, 1988;Beall et al, 1989;. Electron microscopy of IFMs from heterozygous troponin T and actin null mutants revealed that these mutations reduced the number of thin filaments by "o50%, whereas heterozygous myosin heavy chain null mutants exhibit an "o50% reduction in the number of thick filaments.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…If so, a mutation that alters the ratio of thick to thin filaments or affects crossbridge formation would also be expected to cause aberrant myofibrillar assembly. As expected, mutations in the genes encoding myosin heavy chain, troponin T and the IFM specific isoform of actin have been shown to result in aberrant myofibrillar assembly in heterozygotes (Mogami et al, 1981;Mahaffey et al, 1985; Chun and Falkenthal, 1988;O'Donnell and Bernstein, 1988;Beall et al, 1989;. Electron microscopy of IFMs from heterozygous troponin T and actin null mutants revealed that these mutations reduced the number of thin filaments by "o50%, whereas heterozygous myosin heavy chain null mutants exhibit an "o50% reduction in the number of thick filaments.…”
mentioning
confidence: 98%
“…The length of the myofibrils is increased by an increase in sarcomere length, whereas the increase in myofibrillar diameter is due to the addition of Z disc material, thick filaments, and thin filaments at the periphery of the myofibril (Shafiq, 1963;Crossley, 1978;Sanger et al, 1986). Thick filament assembly is independent of thin filament assembly; however, the assembly of both filament systems is required for the proper alignment and registry of Z bands (Mahaffey et al, 1985;Chun and Falkenthal, 1988;O'Donnell and Bernstein, 1988;Beall et al, 1989). It has been proposed that the interaction of thick and thin filaments via the myosin cross-bridge is responsible for the correct registration of the sarcomeres (O'Donnell and Bernstein, 1988;Beall et al, 1989).…”
Section: Ifm Myofibrillar Assembly Requires Diploid Levels Of Mlc-2 Gmentioning
confidence: 99%
See 2 more Smart Citations
“…This highlighted that the analysis of how mef2 functions is central to understanding how muscle is made. Important characteristics of the underlying genetic program include the temporal coordination of muscle gene expression (11)(12)(13) and the regulation of levels and relative stoichiometries of gene expression during myogenesis (14)(15)(16)(17)(18)(19). Although these basic features have been known for many years, much remains to be understood about them.…”
mentioning
confidence: 99%